Complementary tuning semiconductor NCs properties using precursor reactivity, doping, and post-synthetic modification - Yadanparast, Mohammad Sadegh (Kansas State University, 2018)
Quantum dots are nanocrystalline semiconductors in which the size is so small that optoelectronic properties are size dependent. QDs have a lot of applications in displays, solar cells, lasers, light emitting diodes, etc. The optoelectronic properties of QDs depend on their size, composition, the shape of the particles and also the surface chemistry of the QDs. Phosphine based precursors have been mostly used in the synthesis of QDs. Due to the lack of tunable reactivity, this class of precursors, QDs with different shape are obtained by under different reaction conditions. With that, branched QDs are less likely to be obtained in one step reaction using phosphine based precursors. To synthesis QDs with a branched structure, in a single step synthesis, mixtures of precursors with different reactivity were used. Using dichalcogenides mixture, CdSe₁-xSx hyperbranched supra-quantum dots (HSQDs) where synthesized in a one-step microwave-assisted synthesis and shape evolution mechanism of formation of NCs studied. It is shown that the NCs formed in three steps of nucleation, aggregation, and growth. By controlling the reaction conditions, simple branched tetrapod NCs are prepared, but the obtained NCs have no emission due to unpassivated surface and defects which work as trap. To obtain luminescent NCs obtained through doping. Hyperbranched Mn²+:ZnSe₁-xSx NCs also prepared using a mixture of Ph₂Se₂ and Me₂S₂. The shape evolution mechanism of the formation of NCs was studied and it is shown that the NCs are formed via oriented attachment of initially formed nanoparticles. The NCs used for thiol sensing, and it observed that they have a better sensitivity and detection limit than spherical QDs. Although hyperbranched NCs have higher sensitivities over nonbranched NCs but, the spherical NCs have better detection limit and can dispersed in aqueous medium by ZnS shell growth followed by silica shell formation. To study the effect of ZnS shell thickness on sensing property of NCs, a set of spherical Mn:ZnSe@ZnS with different ZnS shell thickness were prepared and used for thiol sensing. It observed that in organic medium, thinner ZnS layer gives the highest sensitivity and QDs with thick ZnS shell layer have less sensitivity. For measurement in aqueous medium, QDs transferred to PBS buffer after formation of silica shell over QDs. It observed that NCs with a thin ZnS shell layer lose their emission and sensing completely. Thick ZnS shell protects NCs in the silica shell formation step but they show very low sensitivity to thiol compounds as well. ZnS shell with medium thickness gives the best sensitivity in an aqueous medium. The emission of Mn:ZnSe@ZnS QDs originated from d-d electron transition of Mn(II) ions and is independent to the size of QDs. To extend our study to QDs with band edge emission, preparation of luminescent InP QDs by post-synthetic modification is studied. InP NCs were synthesized using heat up method and successive injection of precursors. Narrow size distribution NCs obtained after size selection precipitation. Emissive NCs obtained after etching using InCl3 and fluoride containing salts. The study showed that more InCl3 case more etching and presence of fluoride-containing salt is necessary for band edge emission of the NCs.
Keywords: Indium Phosphide; Post-synthetic Etching; Hyperbranched NCs; Thiol sensing; Mn-Doped NCs; Dichalcogenides